2000
DOI: 10.2165/00003088-200039010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions with Cisapride

Abstract: Cisapride, a prokinetic agent, has been used for the treatment of a number of gastrointestinal disorders, particularly gastro-oesophageal reflux disease in adults and children. Since 1993, 341 cases of ventricular arrhythmias, including 80 deaths, have been reported to the US Food and Drug Administration. Marketing of the drug has now been discontinued in the US; however, it is still available under a limited-access protocol. Knowledge of the risk factors for cisapride-associated arrhythmias will be essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 210 publications
2
48
0
2
Order By: Relevance
“…A total of 64% of the patients used drugs for other disorders, mostly cardiovascular (n ϭ 49), psychological (n ϭ 25), and endocrine (n ϭ 14; Tables 1 and 6). Drugs used that may interfere with tamoxifen metabolizing enzymes (36,37) are shown in Table 6. In most cases no significant difference was observed between tamoxifen concentrations in the patients who used concomitant medications as compared with those who used tamoxifen alone.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 64% of the patients used drugs for other disorders, mostly cardiovascular (n ϭ 49), psychological (n ϭ 25), and endocrine (n ϭ 14; Tables 1 and 6). Drugs used that may interfere with tamoxifen metabolizing enzymes (36,37) are shown in Table 6. In most cases no significant difference was observed between tamoxifen concentrations in the patients who used concomitant medications as compared with those who used tamoxifen alone.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, high doses of grapefruit juice were used and similar outcomes have been reported . Serious cardiac adverse effects, such as tachycardia, palpitations, QT prolongation and torsade de pointes, have been associated with high plasma concentrations of cizapride, including 80 deaths (Michalets & Williams, 2000). It appears that a clinically significant outcome may arise from the combination of cizapride and grapefruit juice, and avoidance of this combination is recommended.…”
Section: Sildenafilmentioning
confidence: 99%
“…Michalets et al, suggest that Met, among the other drugs, is a CYP3A4 inhibitor and it should be avoided in coadministration with other CYP3A4 substrates, but there is no confirmation from in vivo studies [21]. Based on detailed research of available database (FDA, EMA, Drugs), according to isolated case reports, Met does not significantly inhibit CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 99%